TRANSFORMASI ADAT RESAM PERNIKAHAN MELAYU JAMBI DI ERA MODERN: KAJIAN LAPANGAN TENTANG PERGESERAN NILAI DAN MAKNA BUDAYA DI DESA OLAK KEMANG - Nirwan ll Yasin; Fatonah Fatonah; Desy Mayang Sari; Andi Fadliyah; Rahelia Rahelia; Sitorus Sitorus; Irfan Pramudya P; Restya Nanda Oktafiana (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to examine the transformation and continuity of traditional wedding customs among the Malay community in Olak Kemang Village, Jambi. Traditional wedding ceremonies reflect the cultural values and social identity of the Malay people, passed down through generations. However, modernization has brought about adaptations in its practice. This research employs a qualitative ethnographic approach through field observations, interviews with traditional leaders, and documentation of wedding ceremonies. The results show that several traditional elements, such as the berinai ritual and the menyambut besan ceremony, have been simplified, while cultural symbols like wedding attire and traditional music remain preserved as identity markers of the Jambi Malays. Modernization affects the form of performance, yet social values such as mutual cooperation, respect for elders, and communal harmony remain at the core.